PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA PROSES PEMBELAJARAN IPAS - Fairuz, Rahmi Septia; Dewi, Ratna Sari; Taufik, M. (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model to improve students’ conceptual understanding in the IPAS learning process for fifth-grade students at SD Negeri Tembong 2. The research used a quantitative method with a nonequivalent control group design. The sample consisted of 48 fifth-grade students. The data collection technique involved tests, including a pre-test and post-test. The data were analyzed using N-Gain scores. The results showed that the improvement in students’ conceptual understanding after the implementation of the Problem-Based Learning model was evident from the N-Gain score in the experimental class, which was 0.72—classified as high. This was better than the students in the control class who received conventional learning, with an N-Gain score of 0.31—classified as moderate.